Towards a Conscious Business future: proposal and application of a multidimensional framework and its effects on stakeholders\' engagement, financial performance and ESG metrics - Paro, Pedro Ernesto Pereira (2023)
This research aims to investigate the relationship between Conscious Business (CB) and its effects on stakeholder engagement, financial performance, and ESG metrics. The sample includes responses from 86,945 stakeholders from 300 Brazilian companies, representing leaders, employees, customers, suppliers, and local communities. The findings indicate that increasing levels of consciousness in business have a positive effect on stakeholder engagement, financial performance, and ESG metrics. Conscious Business has a positive and significant effect on leadership, employee, local community, and environmental caring (p < 0.001), and a low significant effect on customer and supplier (p < 0.10). In comparison, B Corps have a positive and statistically significant effect on local community and environmental care, but no significant effect on leadership, employees, customers, and supplier engagement. The results also show that CB has a positive correlation with financial performance, such as annual growth (r = 0.25) and ROI in 5 years (r = 0.27), as well as with ESG metrics, such as women in leadership (r = 0.42), positive impact in the supply chain (r = 0.69), reduction of greenhouse gas emissions (r = 0.31), and use of renewable energy (r = 0.28). Moreover, analyzing data from the Brazilian stock market, the most conscious organizations evaluated by the study have a financial return 5.52 times higher than the market average. The findings have several practical implications. Measuring and developing leaders and organizations\' consciousness levels can help balance economic, social, and environmental goals. Investment funds can use new criteria for more conscious decision-making, seeking to balance economic returns with environmental and social impact. B Corps can use these findings to improve their communication efforts regarding local community and environmental caring effects and work on their certification process with a focus on improving internal stakeholder engagement, such as leadership and employee engagement, as well as customer and supplier engagement. Finally, this study has practical implications for the UN Global Compact and World Economic Forum, as it provides empirical evidence of the crucial role of leaders and organizations\' conscious levels in promoting a more humane, ethical, innovative, and sustainable business world. This can be used to encourage businesses to prioritize stakeholder engagement as part of their efforts to advance societal goals and achieve sustainable development, aiming to accelerate Sustainable Development Goals (SDGs), Conscious Capitalism, and Stakeholder Capitalism.